A INFLUÊNCIA DA CULTURA NO COMPORTAMENTO DO CONSUMIDOR DE CARNE NA REGIÃO FRONTEIRA NOROESTE - Zamin, Marciela; Sparemberger, Ariosto; Zamberlan, Luciano; Büttenbender, Pedro L.; Wagner, Adriano; Sausen, Jorge O.; Höfler, Cláudio E. (Salão do Conhecimento, 2013)
Resumo